2008
DOI: 10.1007/s10493-008-9175-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of mixed infections in ticks on transmission dynamics of pathogens: comparative analysis of published records

Abstract: Ticks are often infected with more than one pathogen, and several field surveys have documented nonrandom levels of coinfection. Levels of coinfection by pathogens in four tick species were analyzed using published infection data. Coinfection patterns of pathogens in field-collected ticks include numerous cases of higher or lower levels of coinfection than would be expected due to chance alone, but the vast majority of these cases can be explained on the basis of vertebrate host associations of the pathogens, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…Such correlations suggest that the more ticks feed on a lizard, the greater chance of contact with infected ticks, and hence more chance of acquiring tick-borne infection. The results confirmed previous studies [38,39] which show that the probability of host exposure to a tick-borne pathogen is correlated with tick abundance. Therefore, the best way to avoid infection with tick-borne disease is to avoid areas with a high density of its vectors [18].…”
Section: Discussionsupporting
confidence: 91%
“…Such correlations suggest that the more ticks feed on a lizard, the greater chance of contact with infected ticks, and hence more chance of acquiring tick-borne infection. The results confirmed previous studies [38,39] which show that the probability of host exposure to a tick-borne pathogen is correlated with tick abundance. Therefore, the best way to avoid infection with tick-borne disease is to avoid areas with a high density of its vectors [18].…”
Section: Discussionsupporting
confidence: 91%
“…In general, infections of ticks with multiple pathogens can result in co-transmission of various combinations of tick-borne microorganisms to vertebrate hosts, which may have severe implications for human and animal health [154–156]. We assume that co-transmission of the detected microorganisms to ungulates by ticks does not occur in the study area, or it may occur to a very low extent (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that B. burgdorferi s.l. coexists in ticks with some other tick-borne pathogens (Belongia, 2002;Burri et al, 2011;Coipan et al, 2013b;Ginsberg, 2008;Koetsveld et al, 2015;Lommano et al, 2012;Nieto and Foley, 2009;Reye et al, 2010). Likewise, it is known that the severity of LB may be affected by simultaneous infections with other bacteria, such as Anaplasma phagocytophilum (Belongia, 2002;Holden et al, 2005;Swanson et al, 2006;Thomas et al, 2001), that are capable to modulate host immunity and, therefore, increase susceptibility to various second pathogens.…”
Section: Association With Disseminated/persistent Forms Of Lyme Borrementioning
confidence: 99%